The effects of digitalisation on the labour market: the case of Russia. (1st January 2020) - Matraeva, Liliia; Vasiutina, Ekaterina; Belyak, Alexey
Abstract : This article looks at the mechanism of formation of new institutional traps in the labour market under conditions of digitalisation of the economy. In particular, the effects of coordination, training and pairing, as well as cultural inertia and lobbying, are analysed as structural elements of institutional traps, which in the labour market create prerequisites for the consolidation of specific social norms that reduce the overall efficiency of the economic system. It proposes that, when all the effects are implemented synchronously, they complement each other in such a way as to contribute to the formation of institutional traps in the labour market when digital technologies are introduced. This leads to an escalation of risks in the labour market, against the background of an aggravated contradiction between supply and demand, leading to a self-sustaining structural imbalance associated with the introduction of digitalisation tools. The article draws attention to inertia in the process of adaptation of public institutions, which prevents the optimal institutional set up being reached, as there is a contradiction between the previously formed model of behaviour of economic agents and the system of management.